2007
DOI: 10.1002/biot.200700119
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis of 5‐deoxyflavanones in microorganisms

Abstract: Flavanones are the common precursors of plant polyphenolic compounds collectively known as flavonoids. Leguminous plants have evolved a distinct class of flavanone molecules, known as 5-deoxyflavanones that play important roles in their symbiotic interactions. A four-step metabolic circuit was constructed in Escherichia coli with plant genes from heterologous origins: 4-coumarate:coenzyme A ligase from Petroselinum crispum, chalcone synthases (CHS) from Medicago sativa and Petunia x hybrida and chalcone reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 35 publications
0
37
0
Order By: Relevance
“…Our success in fermentative production of plant-specific polyketides by E. coli carrying an artificially assembled phenylpropanoid pathway was the first example to show that a nearly complete biosynthetic pathway in plants was established in a heterologous microorganism for production of flavanones from the amino acid precursors, phenylalanine and tyrosine [5,6]. Later, Yan et al [7] produced 5-deoxyflavanones in E. coli and Beekwilder et al [8] produced a natural raspberry ketone in E. coli. The approach of this type of combining genes from different organisms and designing a gene cluster to produce a bioactive compound leads not only to diversification of both chemical and natural product libraries but also to efficient use of the potential of the host organisms, particularly when microorganisms are used as the hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Our success in fermentative production of plant-specific polyketides by E. coli carrying an artificially assembled phenylpropanoid pathway was the first example to show that a nearly complete biosynthetic pathway in plants was established in a heterologous microorganism for production of flavanones from the amino acid precursors, phenylalanine and tyrosine [5,6]. Later, Yan et al [7] produced 5-deoxyflavanones in E. coli and Beekwilder et al [8] produced a natural raspberry ketone in E. coli. The approach of this type of combining genes from different organisms and designing a gene cluster to produce a bioactive compound leads not only to diversification of both chemical and natural product libraries but also to efficient use of the potential of the host organisms, particularly when microorganisms are used as the hosts.…”
Section: Introductionmentioning
confidence: 99%
“…Among all developed alternatives, microbial synthesis has been proven to be competent and promising. So far, a variety of chemicals, including biofuels, amino acids, and plant secondary metabolites, have been produced by metabolically engineered microorganisms (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…We also found that the hydrolysis of diarylheptanoid glycoside to free diarylheptanoid in culture medium has anti-trypanosomal and apoptotic activities [27], suggesting that isoliquiritigenin is a liquiritigenin precursor. In fact the biosynthetic pathway between isoliquiritigenin to formononetin via liquiritigenin starting from cinnamic acid was confirmed using microorgainisms and G. echinata cell-free system, respectively as shown in Figure 8 [28,29].…”
Section: Activity Of Crude Licorice Extractmentioning
confidence: 81%